Screening for New Primary Cancers in Patients with Metastatic Breast Cancer: A Provincial Analysis of the Choosing Wisely Canada Recommendations - M. Tesch; K. Laing (Current Oncology, 2019)
Introduction: Patients with metastatic cancer have a decreased life expectancy, and with screening and surveillance for new primary cancers, they run the risk of immediate harm with little chance of any benefit. Choosing Wisely Canada therefore recommends that such investigations be avoided in patients with metastatic disease. Methods: We examined cancer screening practices in a subset of patients with metastatic cancer in Newfoundland and Labrador. Patients with metastatic breast cancer seen at the provincial cancer clinic during 2014–2016 were identified from the Newfoundland and Labrador Cancer Registry. For each patient, we assessed whether any one or a combination of screening mammography, Pap (Papanicolaou) test, flexible sigmoidoscopy or colonoscopy, or fecal immunohistochemical test were performed at any point after the diagnosis of metastatic disease. Results: Of 305 patients with metastatic breast cancer, 114 (37.4%) underwent at least 1 screening investigation (mean: 2.92 investigations per screened patient). The most common screening investigations were mammography (n = 197) and Pap test (n = 107). Primary care providers ordered most of the screening investigations (70%); oncology specialists ordered 14%, and other specialists, 12%. Median overall survival for patients with breast cancer after a diagnosis of metastatic disease was 42 months, with a 5-year overall survival of 35.9%. Conclusion: A significant proportion of patients with metastatic breast cancer in Newfoundland and Labrador are still undergoing screening for new primary malignancies, which is discordant with oncology guidelines from Choosing Wisely Canada. Increased education strategies are needed if the Choosing Wisely Canada recommendations are to be implemented into routine clinical practice.